Anxiety symptoms and coping strategies among high school students in Vietnam after COVID-19 pandemic: a mixed-method evaluation - Hoa, Pham Thi Thu; Trang, Do Thi; Lien, Nguyen Thi; Vinh, Ngo Anh (Frontiers in Public Health, 2024)
Introduction The objective of the current study was to examine the rate of high school students at risk of anxiety disorder during the COVID-19 pandemic in Vietnam, as well as the coping strategies utilized within this demographic. Methods An evaluation was conducted through the utilization of mixed methods, consisting of a combination of a cross-sectional study and in-depth interviews. In this study, a sample of 3,910 students from 13 high schools in Hanoi, Vietnam were selected for participation. The measurement of symptoms of anxiety disorder was conducted through the application of the seven-item General Anxiety Disorder (GAD-7) scale. To comprehend the underlying causes of anxiety and the various coping mechanisms employed, in-depth interviews were conducted. Results The findings indicate a prevalence rate of anxiety disorder symptoms among students at 40.6% The prevalence rates of mild, moderate, and severe anxiety symptoms were found to be 23.9%, 10.9%, and 5.8%, respectively. In-depth interviews uncovered multiple sources of anxiety experienced by high school students, namely their academic performance, social interactions, prejudicial attitudes from their social circle, and familial expectations. Numerous coping strategies were then documented. Discussion The current investigation ascertained that there exists a moderate level of anxiety amongst high school students in Hanoi, Vietnam during the COVID-19 outbreak. Furthermore, this study configured potential indicators to identify vulnerable individuals and further suggests the development of targeted interventions.